APPROACHES TO THE FORMATION OF PERSONNEL POLICY IN PUBLIC AUTHORITIES - S. Zudenkova (Вестник университета)
Civil service development is impossible without improving the personnel policies of the public authorities, considered as the core of the personnel management system, which records all procedures and activities undertaken public administrations in respect of the labour force. The basic principles of the personnel policy and a special state authority are revealed the advantages of competence approach to personnel policy are outlined as well as the results of the analysis of foreign experience in forming of personnel policy are given.